Does menopausal transition really influence mental health? Findings from the prospective long‐term Zurich study. Issue 2 (June 2016) - Rössler, Wulf; Ajdacic‐Gross, Vladeta; Riecher‐Rössler, Anita; Angst, Jules; Hengartner, Michael P.
Abstract : In the prospective long‐term Zurich study, we re‐examined the hypothesized association between mental health problems in women and the transition through menopausal stages. One hundred sixty‐eight women from a population‐based Swiss community cohort were prospectively followed up from age 21 to 50. At age 50, the occurrence of hot flushes/night sweats and sleep disturbances was significantly more frequent in peri‐ and post‐menopausal women. Irritability/nervousness was increased only in peri‐menopausal women, but that association was accounted for by neuroticism trait scores at age 30. Transitions to peri‐ or post‐menopause were not related to changes in either the prevalence rates of DSM major depressive episode or anxiety disorders, or the course of psychopathological syndromes as assessed by the Symptom Checklist 90 ‐ Revised. The null associations held when adjusting for duration of reproductive period or age at menopause. Preceding mental health problems between ages 21 and 41, increased neuroticism trait scores at age 30, and concurrent psychosocial distress were significantly related to mental health problems occurring between ages 41 and 50. Depending upon the cut‐off point that was chosen, the arbitrary dichotomization of a continuous depression outcome produced spurious associations with the menopausal transition. We conclude that mental health problems between ages 41 and 50 are probably not directly related to the menopausal transition, and that previously reported associations could be false positives due to inadequate dichotomizations, reporting bias, undisclosed multiple adjustments or overfitting.